THE ROLE OF GENDER IN THE USE OF LANGUAGE IN ONLINE INTERACTIONS: KURDISH INTERLOCUTORS AS NON-NATIVE ENGLISH SPEAKERS - Bikhtiyar Fattah (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ)
This study examines the influence of gender on the use of English by Kurdish as non-native English speakers in online Interlocutors. It aims at figuring out the contributive role of language to the identification of the interlocutors’ gender, determining the influence of cultural norms on shaping the online communication patterns of Kurdish interlocutors(males and females), and identifying the frequency use of the essential linguistic elements, strategies and styles that distinguishes males’ interactions from females’. This study employs a mixed method, quantitative and qualitative, in the process of data analysis. It is quantitative for administrating a Likert-Scale questionnaire to investigate the perceptions of Kurdish as non-native English speakers according to gender and its influence on the interactions conducted online. It is also qualitative for analyzing one hundred instant messages extracted from males and females’ interactions held in three Telegram public channels. The most two significant concluding points that this study has come up with are: (1) gender diversity affects all the aspects of language including word choice, strategy and style in online interactions, and (2) the frequency of using hedge devices, empty adjectives, euphemistic expressions, apologies, justifications, minimal responses, emoticons, tag-questions, rhetorical questions, intensifiers and exclamatory expressions used by females is far more compared to males. However, males use humor and sarcastic expressions far more compared to females.